Place of Prasugrel, P2Y12 receptor antagonist, in an early invasive treatment of patients with acute coronary syndrome (according to the results of multicenter randomized controlled trial ISAR-REACT 5) - S. N. Tereshchenko; M. G. Glezer; S. A. Abugov; O. V. Averkov; S. I. Antipov; A. S. Galyavich; M. Yu. Gilyarov; D. V. Duplyakov; A. A. Efremushkina; D. A. Zateyshchikov; V. V. Ivanenko; E. D. Kosmacheva; et al. (Российский кардиологический журнал)
The conclusion of the Expert Council reports an agreement on the place of the P2Y12 receptor blocker prasugrel in the early invasive treatment of patients with acute coronary syndrome ACS, according to the results of the multicenter randomized controlled study ISAR-REACT 5. Prasugrel should be considered the preferred P2Y12 receptor blocker in the planned primary percutaneous coronary intervention and early invasive management of patients with ST segment elevation ACS. Herewith, prasugrel intake in patients with non-ST segment elevation ACS is preferable after coronary angiography and decision for coronary stenting.